2022
DOI: 10.7861/clinmed.2021-0321
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and venous thrombotic stroke after ChAdOx1 nCoV-19 vaccine

Abstract: Vaccine-induced thrombosis with thrombocytopenia (VITT) is a recently-described condition associated with arterial and venous thrombosis following vaccination with the ChAdOx1 nCoV-19 (AstraZeneca) vaccine. This report describes two cases of stroke caused by arterial and venous thromboses presenting within 28 days of receiving the AstraZeneca vaccine. The patients were otherwise young and healthy with minimal risk factors for thrombosis yet developed a rapid, ultimately fatal neurological deterioration.The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…thrombocytopenia, high D-dimer levels, low fibrinogen, and positive anti-PF4 IgG antibodies). 54,55 These similarities suggest a common pathological pathway related to a coagulopathy induced by the vaccine. Nevertheless, some patients exhibit different paraclinical findings.…”
Section: Arterial Ischemic Strokementioning
confidence: 94%
See 1 more Smart Citation
“…thrombocytopenia, high D-dimer levels, low fibrinogen, and positive anti-PF4 IgG antibodies). 54,55 These similarities suggest a common pathological pathway related to a coagulopathy induced by the vaccine. Nevertheless, some patients exhibit different paraclinical findings.…”
Section: Arterial Ischemic Strokementioning
confidence: 94%
“…Imaging revealed bilateral anterior cerebral artery (ACA) and right middle cerebral artery (MCA) occlusion. 54 Left hemiparesis was also de clinical manifestation in a 79-year-old male, in whom brain magnetic resonance imaging (MRI) showed lacunar infarcts in anterior circulation territories. 53 Similarly, involvement of the proximal segment of MCA was observed in a 51-year-old female who developed right-sided hemiplegia, hemianopia, and global aphasia 7 days after a ChAdOx1-S vaccine.…”
Section: Arterial Ischemic Strokementioning
confidence: 99%
“…Last but not least, there are arterial thromboembolic incidents following the COVID-19 vaccination. Such a study was provided by Wills et al [155]. The authors reported two stroke cases due to arterial and venous thromboses within four weeks following the administration of the AstraZeneca vaccine.…”
Section: Summary Of Reported Literature Cases Of Ultrarare Vitt Compl...mentioning
confidence: 99%
“…Editor -We would like to share ideas on the publication 'Arterial and venous thrombotic stroke after ChAdOx1 nCoV-19 vaccine'. 1 Wills et al concluded that 'These cases illustrate that physicians should be especially mindful of vaccine-induced thrombosis with thrombocytopenia (VITT) in the context of evolving evidence on treatment and in view of the potentially rapid and catastrophic neurological deterioration, leading to fatality despite best supportive care.' We concur that there might be adverse effects of the COVID-19 vaccine and that neurological complication might be a serious one.…”
Section: Overviewmentioning
confidence: 99%